Health literacy–listening skill and patient questions following cancer prevention and screening discussions. (22nd July 2015) - Mazor, Kathleen M.; Rubin, Donald L.; Roblin, Douglas W.; Williams, Andrew E.; Han, Paul K. J.; Gaglio, Bridget; Cutrona, Sarah L.; Costanza, Mary E.; Wagner, Joann L.
Abstract: Objective: Patient question‐asking is essential to shared decision making. We sought to describe patients' questions when faced with cancer prevention and screening decisions, and to explore differences in question‐asking as a function of health literacy with respect to spoken information (health literacy–listening). Methods: Four‐hundred and thirty‐three (433) adults listened to simulated physician–patient interactions discussing (i) prophylactic tamoxifen for breast cancer prevention, (ii) PSA testing for prostate cancer and (iii) colorectal cancer screening, and identified questions they would have. Health literacy–listening was assessed using the Cancer Message Literacy Test‐Listening (CMLT‐Listening). Two authors developed a coding scheme, which was applied to all questions. Analyses examined whether participants scoring above or below the median on the CMLT‐Listening asked a similar variety of questions. Results: Questions were coded into six major function categories: risks/benefits, procedure details, personalizing information, additional information, decision making and credibility. Participants who scored higher on the CMLT‐Listening asked a greater variety of risks/benefits questions; those who scored lower asked a greater variety of questions seeking to personalize information. This difference persisted after adjusting for education. Conclusion: Patients' health literacy–listening is associated with distinctive patterns of question utilization following cancer screening and prevention counselling. Providers should not only be responsive to the question functions the patient favours, but also seek to ensure that the patient is exposed to the full range of information needed for shared decision making.